FORMULATION OF "ALVEMINT" GEL FOR RELIEVING PAIN AND SWELLING IN POSTPARTUM MOTHERS WITH BREAST ENGORGEMENT - Yoga Tri Wijayanti; Martini; Yulyuswarni (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
This study aimed to formulate and evaluate the AlveMint gel preparation containing Aloe vera powder and menthol for relieving pain and breast swelling in postpartum mothers with milk engorgement. The gel was prepared using five formulas with variations in Aloe vera concentration: F0 (0%), F1 (0.25%), F2 (0.5%), F3 (0.75%), and F4 (1%), combined with menthol (0.5%) as an active cooling agent. The preparation process included heating, mixing, and homogenization, followed by the addition of preservative and pH adjustment. The formulated gels were evaluated for organoleptic properties, homogeneity, pH, spreadability, stability, and irritation. All gel formulations exhibited white color, menthol aroma, and semi-solid consistency. The gels were homogeneous, with pH values ranging from 5.1 to 5.5, fulfilling the acceptable skin pH range (4.5–6.5). The spreadability values were between 5.9 and 6.6 cm, meeting the semi-solid dosage form requirements (5–7 cm). No irritation reactions were observed among 15 human volunteers during patch testing. The presence of menthol provided a cooling sensation, enhancing comfort during application. Increasing concentrations of Aloe vera slightly decreased pH values but did not affect the gel’s stability or homogeneity. In conclusion, the AlveMint gel formulation containing Aloe vera and menthol demonstrated good physical properties, acceptable skin compatibility, and potential for use as a topical preparation to alleviate breast engorgement symptoms in postpartum mothers.